2018
DOI: 10.1016/j.foodchem.2017.05.044
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ageing temperature on the physicochemical properties, phytochemical profile and α-glucosidase inhibition of Hibiscus sabdariffa (roselle) wine

Abstract: The effect of temperature (6, 15 and 30°C) during ageing on the colour, phytochemical composition and bioactivity of roselle wine was investigated over 12months. At the end of ageing, wines stored at 6°C had the highest colour density and lowest polymeric anthocyanins. The initial concentration of most of the individual phenolic compounds decreased during ageing, with reduction of monomeric anthocyanins contributing to the formation of anthocyanin-derivatives (pyranoanthocyanins), eight of which were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…The separation of sugar was performed on a Grace Davison Prevail Carbohydrate Es column (5 m, 250 mm × 4.6 mm). The mobile phase was 75 % acetonitrile (v/v) applied at a flow rate of 0.5 mL/min.Total polyphenolic content was evaluated using the Folin and Ciocalteu reagent as described byIfie et al (2017).…”
mentioning
confidence: 99%
“…The separation of sugar was performed on a Grace Davison Prevail Carbohydrate Es column (5 m, 250 mm × 4.6 mm). The mobile phase was 75 % acetonitrile (v/v) applied at a flow rate of 0.5 mL/min.Total polyphenolic content was evaluated using the Folin and Ciocalteu reagent as described byIfie et al (2017).…”
mentioning
confidence: 99%
“…Roselle wine was produced and aged according to previous published methods [9,14]. Briefly, the wine was produced by fermenting dark red Hibiscus sabdariffa calycles at 30 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Volatile composition and anthocyanin content (Table 1) that could influence the sensory rating of the wines were analysed using GC-MS and HPLC methods [9,14].…”
Section: Chemical Parameters Of Winementioning
confidence: 99%
“…The edible calyces can be made into jam, jelly, sauce, and wine; its seeds contain high protein and are used as a food ingredient in Africa . Bioactive ingredients of H. sabdariffa , such as anthocyanins, anthocyanidins with a sugar moiety, gallic acid, syringic acid, caffeic acid, and flavonoids have been widely studied for their antimicrobial, plasma‐cholesterol reducing, and immune‐regulating functions . Studies have also reported that extracts from H. sabdariffa inhibit cancer cell metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…12 Bioactive ingredients of H. sabdariffa, such as anthocyanins, anthocyanidins with a sugar moiety, gallic acid, syringic acid, caffeic acid, and flavonoids have been widely studied for their antimicrobial, plasma-cholesterol reducing, and immune-regulating functions. [13][14][15][16] Studies have also reported that extracts from H. sabdariffa inhibit cancer cell metastasis. 17,18 It is known that flavonoids inhibit oxidative stress in vitro by acting either as free radical scavengers or as metal chelating agents.…”
Section: Introductionmentioning
confidence: 99%